2023
DOI: 10.1088/2634-4386/acc2e1
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on investigation of neurodegenerative diseases with neurorobotics approaches

Abstract: Neurorobotics has emerged from the alliance between Neuroscience and Robotics. It pursues the investigation of reproducing living organism-like behaviours in robots by means of the embodiment of computational models of the central nervous system. 
This perspective article discusses the current trend of implementing tools for the pressing challenge of early diagnosis of neurodegenerative diseases and how neurorobotics approaches can help. Recently, advances in this field have allowed the testing of some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 90 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…In this article, we show that when the tonic level of simulated dopamine in a robot model of the basal ganglia [ 36 ] is significantly reduced or increased, relative to a baseline, a variety of behavioural outcomes are observed that provide interesting comparisons with the results of animal studies, and with some of the observed behavioural consequences of dopamine dysregulation in disorders affecting the human basal ganglia. In this way, we hope that this article can contribute to the emerging field of computational psychiatry [ 37 ] and to the investigation of models of psychopathology via robotics [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we show that when the tonic level of simulated dopamine in a robot model of the basal ganglia [ 36 ] is significantly reduced or increased, relative to a baseline, a variety of behavioural outcomes are observed that provide interesting comparisons with the results of animal studies, and with some of the observed behavioural consequences of dopamine dysregulation in disorders affecting the human basal ganglia. In this way, we hope that this article can contribute to the emerging field of computational psychiatry [ 37 ] and to the investigation of models of psychopathology via robotics [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A historical perspective (Szczecinski et al 2023) gives a gentle introduction into the neuroscientific principles that underlie models and inspire neuromorphic robot controllers for legged robots. The other perspective (Tolu et al 2023) discusses the current trend of implementing tools for the pressing challenge of early diagnosis of neurodegenerative diseases and how brain-body models can help.…”
mentioning
confidence: 99%